Tuning Surface Phonon Polaritons in One‐Dimensional Complementary Nanostructures via Curvature and Dielectric - Li Zhang; Feiyue Lu; Zhiwen Liang; Guanghui Wang; Junjie Shi; Qi Wang (Advanced Photonics Research)
Phonon polaritons (PhPs) in polar crystals have garnered extensive attention due to their excellent characteristics in light‐matter interaction. However, wavelength and frequency band of PhPs are currently quite narrow and heavily dependant on phonon reststrahlen bands of material chosen. In most cases, these reststrahlen bands cannot be fully occupied. Moreover, methods for tuning and manipulating PhPs are rather limited. Herein, an idea of curvature and dielectric is introduced to tune properties of surface phonon polaritons (SPhPs) in quasi‐1‐dimensional complementary nanostructures: nanowire (NW) and nanohole (NH). Numerical results of wurtzite AlN and cubic SiC show that dispersive spectrum of SPhPs can be effectively regulated by curvature and dielectric methods. NH complements frequency band range of SPhP modes of NW structures. NW together with NH accurately occupy the whole reststrahlen band of SPhPs of semiconductors. Furthermore, the frequency‐band subinterval of SPhP in NHs and NWs can be significantly tuned by dielectric. The SPhP dispersion spectrum and wavelength compression ratio in NW and NH structures are inherently self‐consistent. Moreover, calculated results are in good agreement with relevant experimental data. Herein, new ideas are provided for the regulation and manipulation of PhPs in nanostructures.